Long term effect of fertilizers and amendments on the properties of an acid Alfisol and uptake of primary nutrients and sulfur in maize-wheat rotation in North Western Himalayas. (14th September 2019) - , Gourav; Sankhyan, N. K.; Sharma, R. P.; Sharma, G. D.
Abstract: Soil physico-chemical properties and NPKS uptake were studied in a long-term fertilizer experiment at experimental farm of Department of Soil Science, Himachal Pradesh Agricultural University, Palampur (India). All properties were significantly affected by long term application of fertilizers. Bulk density was the highest with 100% N application and the lowest with FYM application. Optimum pH was resulted in lime amended treatment. Organic carbon, CEC, Available N and K were highest in FYM amended treatment. Available P was highest in 150% NPK and that was at par with 100% NPK + FYM. All primary nutrients were decreasing with increasing depth. Application of 100% NPK + FYM recorded highest yield of maize and wheat, which was at par with 100% NPK + lime. Uptake of NPK and S followed the yield trend and resulted in the highest uptake of NPK and S in 100% NPK + FYM and the lowest in control.